The cyclical behaviour of fiscal policy: are developing countries different, and do institutions matter? - Mackiewicz, Michał (Technological and Economic Development of Economy, 2023)
The available empirical evidence shows that fiscal authorities commonly revert to procyclical fiscal policies instead of following the normative prescription of budgetary countercyclicality. The available empirical studies suggest that this phenomenon may be attributed to weak fiscal institutions. Hence, it is often advocated that strengthening institutions in the developing countries is a reliable way to improve the cyclical properties of fiscal policy. In this paper, we challenge this view by showing that the impact of institutions on the cyclical behaviour of fiscal policy is not uniform across all countries and differs significantly between advanced economies and the developing ones. In the latter, the impact of institutions on the quality of fiscal policy proves to be weak, which is in stark contrast to the strong relationship observed in developed economies. This surprising result suggests that the focus on improving institutional quality may be of little help as a tool to increase the countercyclicality of fiscal policy in the developing economies.